Periodontal infections and diabetes mellitus: when will the puzzle be complete? - Evanthia Lalla (Blackwell Synergy, 2007)
Division of Periodontics, Section of Oral and Diagnostic Sciences, Columbia University College of Dental Medicine, New York, NY, USA